2014
DOI: 10.1097/01.ehx.0000451898.46827.f0
|View full text |Cite
|
Sign up to set email alerts
|

Histological study on the effect of nicotine administration on the bone of adult male albino rat and the possible protective role of vitamin E

Abstract: We concluded that nicotine has hazardous effects on bone, and vitamin E has a protective role against nicotine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The passive chronic exposure of rats to cigarette smoke, for 189 days, led to a decrease in BMD and BMC parameters, which in humans is indicative of a predisposition to osteoporosis, as well as an increased risk of fractures (ELSHAWARBI et al, 2014;HERMIZI et al, 2009), reinforcing the already known deleterious effects of smoking. In both humans and animals, these deleterious effects have been related to the ability of cigarette smoke to modify the composition of the intestinal microbiota, inducing, in four weeks, in rats, a decrease in the population of Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The passive chronic exposure of rats to cigarette smoke, for 189 days, led to a decrease in BMD and BMC parameters, which in humans is indicative of a predisposition to osteoporosis, as well as an increased risk of fractures (ELSHAWARBI et al, 2014;HERMIZI et al, 2009), reinforcing the already known deleterious effects of smoking. In both humans and animals, these deleterious effects have been related to the ability of cigarette smoke to modify the composition of the intestinal microbiota, inducing, in four weeks, in rats, a decrease in the population of Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 95%
“…FUNG et al (FUNG et al, 1999)reported that nicotine (active ingredient of cigarettes) reduced vitamin D storage and osteoblast activity in humans. A significant decrease in the area of the diaphysis and parameters that quantify bone resistance (maximum strength), resilience (energy), and concentration of minerals, phosphorus, calcium, and magnesium have also been reported in rats exposed to cigarette smoke (ELSHAWARBI et al, 2014) and are probably due to the effect of nicotine on the expression of the sialoprotein gene, a protein expressed by osteoblasts and having functions in osteogenic mineralization (NASH;PERSAUD, 1989).…”
Section: Parametersmentioning
confidence: 99%
See 3 more Smart Citations